Radon flux density measurement on rock surfaces - Ryzhakova, Nadezhda K.; Almyakov, P. E.; Stavitskaya, Kseniya O.; Bukharova, Oksana V.; Lozhnikov, Philip I. (Atomic energy)
More than half of the dose from all natural sources of radiation is created by radon and its daughter decay products. The radon hazard of a building site is evaluated by measuring the radon flux density. Some researchers involved in radon measurements are now of the opinion that the amount of radon released from the surface is determined by the type of rock. However, radon release from the surfaces of various types of rocks is sparsely studied. This article reports the results of radon flux density measurements performed on the surface of common rocks. Attention is focused mainly on the most typical sedimentary rocks found in populated areas.